2019
DOI: 10.1080/08998280.2019.1647713
|View full text |Cite
|
Sign up to set email alerts
|

Anti-N-methyl-d-aspartate receptor encephalitis triggered by emotional stress

Abstract: A 22-year-old woman presented with disorganized behaviors, restlessness, and subacute decline in mental status in the setting of stress. Extensive workup for autoimmune diseases disclosed positive anti-N-methyl-D-aspartate (NMDA) receptor antibodies. We recommend that fertility preservation should be discussed and stress management should be considered in patients with a history of anti-NMDA autoimmune encephalitis because this can help in preventing relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Rare studies have reported the association between stress and anti-NMDARE, and the mechanism was still unclear [5,23,24]. Obi CA and their colleagues suggested that emotional stress triggered immune dysregulation, which ultimately resulted in anti-NMDARE [4]. The other suggested mechanism was the preexisting anti-NMDAR antibody in the peripheral blood [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rare studies have reported the association between stress and anti-NMDARE, and the mechanism was still unclear [5,23,24]. Obi CA and their colleagues suggested that emotional stress triggered immune dysregulation, which ultimately resulted in anti-NMDARE [4]. The other suggested mechanism was the preexisting anti-NMDAR antibody in the peripheral blood [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The antibodies crosslink NMDAR, change its surface dynamics and interaction with other synaptic proteins, inhibit receptor internalization, and lead to severe impairment of synaptic plasticity and NMDAR network function [2]. It is well known that anti-NMDARE may be associated with teratoma and herpes virus infection [3], and also, there are reports in the literature that stress can induce anti-NMDARE [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Развитие ANMDARE могут спровоцировать герпес [38], грипп [39], коронавирусная инфекция COVID-19 [40,41], вакцинация против COVID-19 [40,41], вакцинация против дифтерии, столбняка, коклюша и полиомиелита [42], криптококковый менингит [43], демиелинизирующий процесс [44], послеродовая гормональная перестройка [45], иммунотерапия после трансплантации органов [46], эмоциональный стресс [47] -одним словом, любое состояние, сопровождаемое энергичным иммунным ответом [28,31], и это веский аргумент в пользу идиопатической природы заболевания.…”
unclassified